Hatha yoga, integrating the segmental stabilization exercise model, can improve trunk muscle endurance in healthy adults - Petrič, Maja; Zaletel-Kragelj, Lijana; Jakovljević, Miroljub; Vauhnik, Renata (Frontiers in Public Health, 2024)
IntroductionLow back pain is a very common symptom worldwide and an increasingly important public health problem. Exercises to stabilize the lumbar spine and pelvis have been shown to be effective in preventing or reducing the risk of low back pain. Hatha yoga practice is now increasingly appearing in prevention research and has the potential to improve trunk muscle endurance. The prevention research on endurance training of trunk muscle lacks evidence. The aim of this study was to investigate the effectiveness of a professional and scientifically based exercise program to improve and balance trunk muscle endurance in healthy adults.MethodsA non-randomized control study was conducted. Participants were healthy adults without low back pain or injury who had not performed exercises to improve trunk muscle endurance prior to participation in the study. An analysis of the proposed exercise program’s effectiveness was conducted. The participants were divided into two groups: the exercise group (EG) performed a three-month hatha yoga exercise program (60 min twice a week) that included the spinal and pelvic segmental stabilization exercise model, or the control group (CG), in which participants were asked to maintain their previous lifestyle during the study period. Trunk muscle endurance was measured at baseline (PRE) and after completion of the exercise program (POST) in both groups. The changes in the measured variables were analyzed (PRE-POST analysis, EG-CG comparison).ResultsSeventy-two subjects (nEG = 36, age 32.2 ± 6.8 years; nCG = 36, age 29.9 ± 7.8 years) participated in the study. After the exercise program, the EG participants had significantly better results in endurance in three of the four trunk muscle groups (p < 0.05), but not in any of the endurance ratios.ConclusionHatha yoga when integrating the segmental stabilization exercise model can significantly improve the endurance of at least three of the four major trunk muscle groups. For clinical relevance, the long-term effects of the proposed exercise program should be investigated in individuals with low back pain.